Barons, brokers, and buyers the institutions and cultures of Philippine sugar - Billig, Michael S. 1956- (Honolulu, Hawaii University of Hawaii Press, 2018)
This innovative ethnography takes a new approach to the study of Philippine sugar. For much of the late colonial history of the Philippines, sugar was its most lucrative export, the biggest employer, and the greatest source of political influence. The so-called "Sugar Barons"--wealthy hacendero planters located mainly in Central Luzon and on the Visayan island of Negros--gained the reputation as kingmakers and became noted for their lavish lifestyles and the quasi-feudal nature of their estates. But Philippine sugar gradually declined into obsolescence; today it is regarded as a "sunset industry" that can barely satisfy domestic demand. While planters continue to think of themselves as wielding considerable power and influence, they are more often seen as vestiges of a bygone era.
The legacy of colonialism and neo-colonialism -- Production, financing, CARP, and the U.S. quota -- Property rights, Quedans, and the SRA -- The great importation war -- Rationalization, groupism, and the Chinese -- Conclusion : the institutions and cultures of Philippine sugar.
Includes bibliographical references and index.
Keywords: Sugar trade -- Philippines; Sugarcane industry -- History. -- Philippines; Economic anthropology -- Philippines